Mapping and comparing French people's positions regarding restrictive control policies: a pilot study - Sylvie Castanié; Maria Teresa Munoz Sastre; Lonzozou Kpanake; Etienne Mullet (BMC, 2020)
Abstract Background Public authorities resort to various control policies in order to curb the prevalence of unhealthy behaviors. As these policies can only succeed to the extent that people agree with them, this study mapped French people's positions regarding restrictive control policies in general. Method A sample of 344 adults (among them health professionals and lawyers) were presented with 54 vignettes depicting a control policy. Each vignette contained four pieces of information: the type of addictive behavior targeted (smoking, drinking, or gambling), the nature of preventive measures (e.g., information campaigns), the degree of regulative measures (e.g., prohibition to minors), and the severity of sanctions. Results Through cluster analysis, eight qualitatively different positions were found: Never acceptable (9%), Weak or moderate regulation (5%), Moderate regulation associated with strong prevention (11%), Strong or moderate regulation (11%), Strong regulation in association with strong prevention (23%), Moderate sanctions in association with strong prevention and moderate regulation (9%), Severe sanctions (9%), and Always acceptable (9%). Some participants (14%) expressed no opinion at all. Conclusion French people's positions regarding control policies were extremely diverse. Regarding tobacco, however, one type of policy would likely be supported by a majority of people: Moderate regulation associated with at least a moderate level of prevention and low-level sanctions. Regarding alcohol, an acceptable position would be: Moderate regulation associated with at least a moderate level of prevention and high-level sanctions. Regarding gambling, an acceptable position would be: Strong regulation associated with at least a moderate level of prevention and low-level sanctions.